Conformational stability of cyclopropanecarboxaldehyde is ruled by vibrational effects. (17th November 2021) - Alessandrini, Silvia; Melosso, Mattia; Jiang, Ningjing; Bizzocchi, Luca; Dore, Luca; Puzzarini, Cristina
Abstract : Cyclopropanecarboxaldehyde (CPCA) has two main conformers, syn and anti, that are renowned for being very close in energy. The stability order of these two main species is constantly reversed by changing the level of theory or the experimental technique employed in its determination. The anti conformer is predicted to be the most favoured in condensed states of matter, but uncertainty still remains on the relative stability in the gas phase. To gain further insights into this issue, the investigation of the rotational spectrum of both syn - and anti -CPCA has been extended in the 246–294 GHz frequency region and complemented by a detailed computational study of both conformers. A fit incorporating the recorded rotational transitions as well as those reported in the literature led to the accurate determination of the rotational parameters, also including high-order centrifugal distortion constants. Accurately computed vibrational frequencies were used to re-analyse the infrared spectrum of both conformers, thereby allowing a re-assignment of two vibrational bands, namely ν 4 of anti -CPCA and ν 26 of the syn conformer. While our state-of-the-art computations favour the anti conformer in the stability order, estimates from analysis of rotational spectra are rather controversial and are strongly affected by several factors, such as the zero-point vibrational correction. GRAPHICAL ABSTRACT: UF0001